On stability of a new side cut destructive method for measuring non-uniform residual stress in thin plates. (1st December 2016) - Kim, H.K.; Shterenlikht, A.; Pavier, M.J.; Velichko, A.; Alexander, N.A.
Highlights: Stability and sensitivity analyses of a recently proposed destructive technique for residual stress measurement are presented. Cutting induced plastic strain can be minimised by choosing suitable propagation of the cut. 3D digital image correlation was used to measure relaxation displacement fields. Residual stress in a 3 mm thick friction stir welded plate was measured with the technique. The measured residual stress was compared with energy dispersive X-ray diffraction. Abstract: Stability and sensitivity analyses of a recently proposed mechanical strain relaxation method for residual stress measurement in thin plates are presented. The method is based on the Mathieu series solution for a semi-infinite elastic strip with self-equilibrated end loading. The effects of the specimen length, incomplete displacement data and rigid body rotation errors were analysed. The results of this analysis were applied to improve the performance of the method for the measurement of the residual stress in a 3 mm thick friction stir welded plate of Aluminium 5083-O alloy. A through cut was introduced with an electrical discharge machining (EDM) wire. 3D digital image correlation was used to measure the relaxation displacements. The reconstructed residual stress profile agrees with that measured by energy dispersive X-ray diffraction (EDXRD). It is shown that the orientation of the EDM wire with respect to the plate significantly affects cutting induced plastic strain. This strain is minimised when the EDM cut is through the thickness of the plate, i.e. when the plate width direction is parallel to the EDM wire. Such orientation of the EDM wire leads to a minimal induced-plasticity on the cut surface. This is a major strength of the method, which makes it attractive in practical applications where other mechanical stress relaxation methods suffer from plastic flow on cutting.